2020
DOI: 10.1186/s13213-020-01545-0
|View full text |Cite|
|
Sign up to set email alerts
|

Production of high-value bioproducts enriched with γ-linolenic acid and β-carotene by filamentous fungi Umbelopsis isabellina using solid-state fermentations

Abstract: Solid-state fermentation is a useful tool for utilizing different plant-based materials as cultivation substrates in order to produce potentially high-value fermented bioproducts. The aim of the present study was to successfully prepare various types of such bioproducts, using a zygomycetous strain Umbelopsis isabellina CCF2412. Various legume and cereal substrates were utilized effectively, while a few of them were obtained from agricultural waste, which is particularly advantageous from ecological and econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…In recent years, several studies have been published, which detail the use of filamentous fungi in SSF and its successful application in broiler nutrition. Specific examples include the use of Umbelopsis isabellina CCF2412 on cornmeal [ 7 , 10 , 11 ], Trichoderma pseudokoningii on wheat bran [ 4 ], Acremonium charticola and Rhizopus oryzae on cassava pulp [ 3 ], Cunninghamella elegans CCF 2591 on spelt brans [ 12 ], Trichoderma viride on copra meal [ 13 ], and Trichoderma virens on palm-fruit husk [ 14 ]. Čertík et al [ 15 ] observed that SSF with Cunninghamella echinulata ATHUM 4411 produces mainly gamma-linolenic acid (18:3, GLA).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have been published, which detail the use of filamentous fungi in SSF and its successful application in broiler nutrition. Specific examples include the use of Umbelopsis isabellina CCF2412 on cornmeal [ 7 , 10 , 11 ], Trichoderma pseudokoningii on wheat bran [ 4 ], Acremonium charticola and Rhizopus oryzae on cassava pulp [ 3 ], Cunninghamella elegans CCF 2591 on spelt brans [ 12 ], Trichoderma viride on copra meal [ 13 ], and Trichoderma virens on palm-fruit husk [ 14 ]. Čertík et al [ 15 ] observed that SSF with Cunninghamella echinulata ATHUM 4411 produces mainly gamma-linolenic acid (18:3, GLA).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we found that the guts of Phylloicus, Triplectides and Stenochironomus larvae analyzed in this study are colonized by Cladosporium, Gliocephalotrichum, Penicillium, Pestalotiopsis, Talaromyces Benjamin, Trichoderma and Umbelopsis fungi that have species that are traditionally used in biotechnological applications (Jalmi et al 2012;Copete-Pertuz et al 2019;Geetha et al 2019;Liuzzi et al 2019;Salazar-Cerezo et al 2019;Ge et al 2020;Slaný et al 2020).…”
Section: Discussionmentioning
confidence: 57%
“…A specific fermentation process called solid-state fermentation (SSF) is a well-described process using a solid matrix and almost no water, accompanied by a high-production capacity [ 11 , 12 ]. Application of SSF with Zygomycetes fungi as a main production cell factories allow acquiring of bioproducts enriched with various long-chain unsaturated fatty acids [ 6 , 13 , 14 ] and also other specific valuable products, such as glucosamine [ 15 ], carotenoid pigments [ 6 , 16 , 17 , 18 ], coenzymes [ 19 ], etc. Furthermore, the process of SSF often leads to the increased enzyme activity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fungus Umbelopsis isabellina , used in this study, is a relatively well-known Zygomycetes species for application in bioremediation [ 29 , 30 ] and fermentation processes [ 16 , 17 , 31 ]. Its ability to effectively produce long-chain fatty acid and carotenoid pigments was described previously [ 16 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation